Stakeholders, stakeholder theory and Corporate Social Responsibility (CSR) - Hart Okorie Awa; Willie Etim; Enyinda Ogbonda (International Journal of Corporate Social Responsibility (JCSR), 2024)
Complacency is almost archaic in the knowledge economy, because firms are overwhelmingly confronted with diverse expectations from better informed stakeholders, who pressure on societal issues amid shareholders' calls for greater financial security. Similarly, there is a growing call for corporations to redefine their responsibilities to stakeholders, and to integrate socio-economic and environmental concerns into business processes and strategies in order to transparently impact on societies. In a bid to support mutually beneficial relationships, this paper shows how stakeholder theory proactively moderates the strength of CSR in social interactions, environmental protection, and sustainable development. It proposes a four-stage stakeholder dialogue ladder which attempts to synergize CSR, stakeholder and stakeholder theory based on the stages as defined by the firm's extent of development, and her regularity and intensity of interaction with stakeholders. The paper argues that subject to the problem to solve, the languages of CSR and stakeholder theory are useful and that, the dichotomies of covering wrongdoing and creating falsehoods could be addressed when firms adopt stakeholder dialogue and collaboration that aid friendly CSR programmes. Thus, the relationship turns that of dyadic partnership, because corporations follow issue or purpose-based CSR programmes that create values that trickle to interdependent stakeholders. In sum, corporations need to continually get committed to environmentally-sensitive CSR since there is a strong relationship between CSR activities, stakeholders and actual performance.
Keywords: 650; CSR; Stakeholder theory; Stakeholders